Empowering women, enhancing nutrition, and ending poverty: IFPRI and Canada - International Food Policy Research Institute (International Food Policy Research Institute, 2018)
Global changes with wide-reaching impacts include rapid urbanization, climate change, conflict-driven migration, and dietary transitions as well as uncertainty regarding trade and foreign investment. More than ever, responding to these challenges will require a systems-oriented, multidisciplinary approach to reshaping agriculture and food systems so that they work for everyone. IFPRI will spearhead research to understand and address these trends, build evidence for sound policies at the country and regional levels, and continue to focus on empowering women. IFPRI’s long-standing partnership with Canada has generated cutting-edge research in support of improved food security and nutrition, particularly for women and children, and gender equity, and IFPRI looks forward to continuing to work together to end hunger and malnutrition.